Cell response of Chlamydomonas actinochloris culture to repeated microwave irradiation - OLESIA O. GRYGORIEVA; MARIANNA A. BEREZOVSJKA; OLEXANDER I. DACENKO (Smujo International, 2015)
Abstract. Grygorieva OO, Berezovsjka MA, Dacenko OI. 2015. Cell response of Chlamydomonas actinochloris culture to repeated microwave irradiation. Nusantara Bioscience 7: 38-42. Two cultures of Chlamydomonas actinochloris Deason et Bold in the lag-phase were exposed to the microwave irradiation. One of them (culture 1) was not treated beforehand, whereas the other (culture 2) was irradiated by microwaves 2 years earlier. The measurement of cell quantity, as well as measurement of change of intensities and spectra of cultures photoluminescence (PL) in the range of chlorophyll a emission, was regularly conducted during the cell cultures development. Cell concentration of culture 1 exposed to the microwave irradiation for the first time has quickly restored while cell concentration of culture 2 which was irradiated repeatedly has fallen significantly. The following increasing cell concentration of culture 2 is negligible. Cell concentration reaches the steady-state level that is about half of the cell concentration of control culture. Initially, the PL efficiency of cells of both cultures decreases noticeably as a result of irradiation. Then there is the monotonic increase to the values which are significantly higher than the corresponding values in the control cultures. The ratio of the intensities at the maxima of the main emission bands of chlorophyll for control samples of both cultures remained approximately at the same level. At the same time effect of irradiation on the cell, PL spectrum appears as a temporary reduction of this magnitude.